Cyberculture, internet and health mobile - Rodríguez Gómez, Rodolfo (Universidad y Salud, 2017)
Introduction: In light of new technologies, the health area faces new scenarios that are transforming the world. One of these is the mobile health that has gone from being a utopia to a reality. To get to know the areas of electronic health and mobile health, it is essential to understand the background in which these advances are developed. This context is framed in the Internet, cyberculture and collective intelligence which are built on the basis of the complexity of action and human interaction. Objective: To analyze the transcendence of key concepts to understand the underlying of mobile health. Materials and methods: A documentary review of physical texts and electronic databases was made. Results: The information was structured in three categories: the first one was culture, cyberspace and collective intelligence; the second one was action, interaction and the Internet, and the last one was mobile health and apps. Conclusions: For the current Society of information and knowledge, cutting-edge areas such as the Internet and mobile devices are more than a technological trend. They have become axes of innovation and construction of the future. Technology offers fascinating possibilities; however, it is important to find a deeper sense of scientific developments that can change the world as mobile health.